PERKEMBANGAN SINTAKSIS ANAK USIA EMPAT TAHUN SEMBILAN BULAN (KAJIAN PSIKOLINGUISTIK) - Kerin Theresa Saragih; Putri Putri; Fitriani Lubis; Lastri Sintauli Siahaan (FKIP, Universitas Palangka Raya, 2023)
With a measurement tool to determine the development of language syntax in children using MLU calculations, researchers will examine language acquisition in children aged four years and nine months through the utterances they speak every day. The method used in this research is descriptive qualitative. Based on the results of an analysis of a child aged 4 years and 11 months named Arya, the results of the calculation of MLU 3.11 are at stage VII, which means it is still at a low stage. At 4 years and 11 months he should be in stage X. Arya is already able to pronounce ten types of words, he is able to speak using complete sentences and is able to speak to form basic sentence patterns, namely S-P-O-K.